2004
DOI: 10.1590/s0100-879x2004001100008
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the prevalence of anti-glutamic acid decarboxylase autoantibodies and duration of type 1 diabetes mellitus in Brazilian patients

Abstract: The objective of the present study was to determine whether the duration of disease has any influence on the prevalence of glutamic acid decarboxylase autoantibodies (GADA) in Brazilian patients with type 1 diabetes (T1D) and variable disease duration. We evaluated 83 patients with T1D. All participants were interviewed and blood was obtained for GADA measurement by a commercial radioimmunoassay (RSR Limited, Cardiff, UK). Four groups of patients were established according to disease duration: A) 1-5 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…Cross‐sectional studies from outside of Europe and North America generally support an effect of ethnicity on autoantibody prevalence, but large studies of populations of non‐European origin are required. Overall lower GADA and IA‐2A prevalence has been reported after diagnosis, compared with people of Northern European origins, for Tanzania, 41 the Philippines 42 and Taiwan, 43 but not for Brazil (GADA only) 44 . A lower ZnT8A prevalence has been reported South African populations 45 .…”
Section: What Factors Affect Islet Autoantibodies After Diagnosis?mentioning
confidence: 88%
“…Cross‐sectional studies from outside of Europe and North America generally support an effect of ethnicity on autoantibody prevalence, but large studies of populations of non‐European origin are required. Overall lower GADA and IA‐2A prevalence has been reported after diagnosis, compared with people of Northern European origins, for Tanzania, 41 the Philippines 42 and Taiwan, 43 but not for Brazil (GADA only) 44 . A lower ZnT8A prevalence has been reported South African populations 45 .…”
Section: What Factors Affect Islet Autoantibodies After Diagnosis?mentioning
confidence: 88%
“…A recent study in Southern Brazil found 63% of GADA positivity in patients with type 1 DM duration between three and five years. 31 On the other hand, the study of Rodacki et al 32 described GADA positivity prevalence of 45.8% of type 1 diabetes patients with a mean duration of disease of 10 y, not affected by disease duration or age at diagnosis. The authors speculate that this low positivity may be due to the fact that only patients with more than one-year of diabetes duration were included in the analysis.…”
Section: Discussionmentioning
confidence: 98%
“…25 The Figure 1 shows that GAD65Ab remains detectable in blood long time after the diagnosis of type 1 diabetes with a peak of 100% observed after 6 years of T1D. Therefore, the investigation of GAD65Ab is very useful to identify the latent autoimmune diabetes cases in adult (LADA).…”
Section: Discussionmentioning
confidence: 99%